Plano de ação para segurança e saúde em canteiros de obras com base em diagnóstico da pandemia da COVID-19 - Rocha, Leonardo Brian Gonçalves da (2023)
The COVID-19 pandemic was considered a humanitarian crisis for the entire world population. The construction industry went through significant challenges related to the health and safety of its workers, having to adapt to new changes and practices recommended by organizations and governmental entities. This research proposes an action plan for construction companies to face new pandemics based on the health and safety measures implemented during the COVID-19 pandemic. The methods used were a literature review in the context of COVID-19 and workers' health, followed by a diagnosis of two surveys developed by the Social Service of Civil Construction of the State of São Paulo (SECONCI-SP) and the Brazilian Chamber of the Construction Industry (CBIC) which collected information on the impacts and safety measures implemented in engineering companies. The results revealed that the number of works in progress in the first two years of the pandemic remained stable; there was a 4% reduction in permanent workers working in the first year and 1% in the second year. There was a 45% reduction in the number of workers on leave suspected of having COVID-19 in the second year, while the number of workers on leave due to being considered a risk group was higher in 2021 (35% more compared to 2020). Around 79% of companies said they had suffered some impact related to the pandemic. Furthermore, a questionnaire or a practice investigation protocol was drawn up and applied to a construction company in the interior of São Paulo. As a result of the research, an action plan is presented that presents several measures, including training employees regarding the prevention and early diagnosis of the disease, daily measurement of their temperature, taking time off when necessary, providing disposable or fabric masks and uniforms, increased individual and environmental hygiene, favoring natural ventilation and division of activities on the construction site, aiming to maintain distance between workers. It was concluded that in a new pandemic scenario, it would be essential to absorb the previous experience and implement good safety practices at the construction site since this is the central place for thousands of construction workers live together.